A Framework On Collaborative Learning Activities To Actively Engage Students In Learning Management System - Mohd Azlim, Mastura (UTeM, 2016)
Learning management system is an electronic learning platform to deliver, monitor and manage learning. However, past research showed less engagement among students in building knowledge because often times the students are treated as mere technology users. In addition, many instructors do not fully utilise the tools provided in the learning management system (LMS) and have use it only to upload notes and announcement. The purpose of this study is to introduce the implementation framework named Collaborative Learning Activities Framework (CLAF) into LMS that can help the instructors to fully utilise the tools in LMS by constructing collaborative learning activities. This framework also aims to increase students’ engagement in the learning activities provided. This study involves 119 students and 30 lecturers from Universiti Teknikal Malaysia Melaka (UTeM), Melaka. The separate pre-post engagement research design was implemented to assess the effectiveness of the framework in increasing students’ engagement. These students were divided into three classes and their engagement is assessed for comparison between LMS learning environment without CLAF. This study implemented questionnaires, semistructured interview, structured observation rubric and pre-post engagement questionnaire. The study found that students show higher active engagement in the LMS with CLAF as compared to the LMS without CLAF. The assessment of the engagement is made based the elements of Engagement Theory. In addition, a training session has been conducted together with instructors to expose them to CLAF. After that, they were asked to answer questionnaires regarding their motivation towards the framework. The instructors showed good motivation to apply the framework but have requested for the design of the framework to be more interactive. The main findings of this study found that the CLAF design which is infused with Engagement Theory can improve instructors’ motivation to utilise the tools in LMS and engage students actively in online collaborative learning activities. The study also found that CLAF is able to helps instructor constructing collaborative learning activities more efficient. This study has contributed in constructing research instruments based on Engagement Theory.